Effect of intraoperative nerve monitoring on postoperative vocal cord palsy rates after thyroidectomy: European multicentre registry‐based study. Issue 5 (16th June 2020) - Staubitz, J. I.; Watzka, F.; Poplawski, A.; Riss, P.; Clerici, T.; Bergenfelz, A.; Musholt, T. J.; ,
Abstract : Background: Intraoperative nerve monitoring (IONM) of the recurrent laryngeal nerve (RLN) predicts the risk of vocal cord palsy (VCP). IONM can be used to adapt the surgical strategy in order to prevent bilateral VCP and associated morbidity. Controversial results have been reported in the literature for the effect of IONM on rates of VCP, and large multicentre studies are required for elucidation. Methods: Patients undergoing first‐time thyroidectomy for benign thyroid disease between May 2015 and January 2019, documented prospectively in the European registry EUROCRINE®, were included in a cohort study. The influence of IONM and other factors on the development of postoperative VCP was analysed using multivariable regression analysis. Results: Of 4598 operations from 82 hospitals, 3542 (77·0 per cent) were performed in female patients. IONM was used in 4182 (91·0 per cent) of 4598 operations, independent of hospital volume. Postoperative VCP was diagnosed in 50 (1·1 per cent) of the 4598 patients. The use of IONM was associated with a lower risk of postoperative VCP in multivariable analysis (odds ratio (OR) 0·34, 95 per cent c.i. 0·16 to 0·73). Damage to the RLN noted during surgery (OR 24·77, 12·91 to 48·07) and thyroiditis (OR 2·03, 1·10 to 3·76) were associated with an increased risk of VCP. Higher hospital volume correlated with a lower rate of VCP (OR 0·05, 0·01 to 0·13). Conclusion: Use of IONM was associated with a low rate of postoperative VCP. Abstract : The influence of intraoperative nerve monitoring (IONM) and other factors on the development of postoperative vocal cord palsy (VCP) was assessed using multivariable regression analysis. In a cohort of 4598 patients from 82 hospitals, IONM was used in over 90 per cent of those treated by primary thyroidectomy for underlying benign thyroid disease. IONM reduced the rate of postoperative VCP. Intraoperative nerve monitoring associated with lower rates of vocal cord palsy Abstract : Antecedentes: La monitorización nerviosa intraoperatoria ( intraoperative nerve monitoring, IONM) del nervio laríngeo recurrente ( recurrent laryngeal nerve, RLN) predice el riesgo de parálisis de la cuerda vocal ( vocal cord palsy, VCP). La IONM se puede utilizar para adaptar la estrategia quirúrgica con el objetivo de prevenir la VCP bilateral y la morbilidad asociada. La literatura describe resultados controvertidos de la influencia de la IONM sobre las tasas de VCP, por lo que se requieren grandes estudios multicéntricos para aclararlo. Métodos: De mayo de 2015 a enero de 2019, las tiroidectomías efectuadas como primera intervención quirúrgica por patología tiroidea benigna – documentadas prospectivamente en el registro europeo EUROCRINE © – se incluyeron en un estudio de cohortes. La influencia de la IONM y otros factores sobre el desarrollo de VCP postoperatoria fueron analizados utilizando un análisis de regresión multivariable. Resultados: De 4.598 operaciones efectuadas en 82 hospitales e incluidas en el estudio, 3.542 (77, 0%) fueron realizadas en mujeres. La IONM se utilizó en 4.182 de 4.598 (91, 0%) operaciones independientemente del volumen del hospital. La VCP postoperatoria se diagnosticó en 50 de 4.598 (1, 1%) pacientes. La utilización de IONM se asoció con un menor riesgo de VCP postoperatoria en el análisis multivariable (razón de oportunidades, odds ratio, OR 0, 34 (i.c. del 95% 0, 16‐0, 73)). La detección de lesión del RLN durante la cirugía (OR 24, 77 (12, 91 a 48, 07)) y la tiroiditis (OR 2, 03 (1, 10 a 3, 76)) se asociaron con un riesgo aumentado de VCP. Un elevado volumen de casos se correlacionó con menor frecuencia de VCP (OR 0, 05 (0, 01 a 0, 13)). Conclusión: La utilización de la IONM se asoció con una baja tasa de VCP postoperatoria.